2013
DOI: 10.3928/01477447-20130724-03
|View full text |Cite
|
Sign up to set email alerts
|

Delamination of Tantalum Porous Coating From a TKA Due to Regional Dissemination of Debris

Abstract: Metallic debris from metal-on-metal bearings is a recognized mode of failure that may lead to implant loosening and periprosthetic soft tissue reactions. The sequelae of metallosis have been most commonly reported with respect to total hip arthroplasty. The authors report a rare case of metallosis following a hybrid metal-on-polyethylene total knee arthroplasty that used a porous tantalum tibial knee component. A total knee arthroplasty patient who presented with knee pain but normal radiographs was found to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…23 Zhu et al 4 reported a release of ,2 μg/L Ta from Ta films deposited on sand-blasted, large grit, and acid etched (SLA) Ti surfaces after immersion in PBS for 28 days. Bonutti et al 24 reported a case of metallosis following a total knee arthroplasty (TKA) that used a porous Ta tibial knee component. The patient's operation employed a revised TKA, and delamination of the tibial component was found.…”
Section: Introductionmentioning
confidence: 99%
“…23 Zhu et al 4 reported a release of ,2 μg/L Ta from Ta films deposited on sand-blasted, large grit, and acid etched (SLA) Ti surfaces after immersion in PBS for 28 days. Bonutti et al 24 reported a case of metallosis following a total knee arthroplasty (TKA) that used a porous Ta tibial knee component. The patient's operation employed a revised TKA, and delamination of the tibial component was found.…”
Section: Introductionmentioning
confidence: 99%
“…There are simply many more examples of THA trunnionosis to observe and collect data on. However, while this may be true there is at least some evidence that the prevalence of trunnionosis in TKA may be larger than currently reported [23][24][25][26][27][28] . The underreporting of trunnionosis in TKA only amplifies the growing disparity in the literature regarding trunnionosis in TKA vs THA.…”
Section: Why Trunnionosis Is Studied Less In Tka Vs Thamentioning
confidence: 76%
“…The treatment for trunnionosis in TKA is similar to that of THA [18] . The prosthetic removal, the soft tissue debridement for those regions affected by ARMD, and the subsequent revision is the mainstay of treatment [4,23,24] .…”
Section: Similarities Of Trunnionosis Between Tka and Thamentioning
confidence: 99%
“…Additionally, with increasing porous Ta implantation duration, the Ta particle content in rat bone tissues shows a gradual upward trend. Research by Fokter and Bonutti also reported that during clinical follow‐ups after porous Ta implantation, [ 35,36 ] X‐ray images showed high‐signal granular materials, and black granular deposits were observed during surgery under direct vision. Therefore, Understanding how Ta particles affect bone metabolism and their interaction with bone remodeling and disease is critical for the long‐term efficacy of porous Ta implants.…”
Section: Resultsmentioning
confidence: 98%